Makna Teologis Kata Perhentian dalam Ibrani 4:1-14 (Analisis Tekstual, Stuktural, Kontekstual dan Intertekstual) - Daniel Lindung Adiatma; Saul Arlos Gurich (Sekolah Tinggi Teologi Kalimantan, 2021)
There is a tendency for many commentators of the New Testament to interpret the text with a topical approach. This approach is relevant for research in the field of Christian theology. The problem is, that the topical approach has a tendency to ignore the unity of the elements of the book. Therefore, we need a model of topical interpretation that is perfected with the unity of the theology of the book. The topic of the theological meaning of the word